PROTECTION OF CURRENCY BY THE EUROPEAN AND DOMESTIC CRIMINAL LAW - Sántha, Ferenc (European Integration Studies, 2019)
Crimes committed againts the order and security of cash-flow, as endangering the monetary interests of the state, are among the oldest criminal offences: money counterfeiting exist as long as money itself. Crime of counterfeiting money was considered as one of the most serious delictums in the Roman Law that violates the public confidence and public credibility. Moreover, counterfeiting currency were punished by severe sanctions, often by death penalty, in every historic period and in every country. Criminal prosecution of these types of crimes is independent from the actual economic policy and the prohibition under criminal law is ethically justified.3 The real threat of this crime is the damage it can cause to the economy. High numbers of fake money in the circulation can destabilize the economic relations and trust in a country’s money.